THE INFLUENCE OF GREEN IMAGE, GREEN COMMUNICATION ON SUSTAINABILITY REPORT WITH FINANCIAL PERFORMANCE VARIABLES AS MODERATION - Tamrin Lanori; Usmar; Selfiani (ZILLZELL MEDIA PRIMA, 2023)
This study aims to examine the effect of green image and green communication on sustainability report with the financial performance as a moderating variable. This research method uses quantitative and secondary data. The sample used in this study is manufacturing companies listed on the IDX in 2020 with the measurement of sustainability report, green image using an index, green communication using an index, and financial performance. Specific objectives: To analyze and examine the effect of green image on Sustainability Report, the effect of green communication on Sustainability Report, the effect of financial performance moderating the relationship between green image and Sustainability Report, the effect of financial performance moderating the relationship between green communication and Sustainability Report.Research Method: Population and sample are manufacturing companies using data analysis methodology, namely descriptive statistics, assumption tests, data normality tests to hypothesis testing. Research Results: Green Image is proven to have a positive effect on Sustainability Report, Green Communication is proven to have a positive effect on Sustainability Report, Financial Performance moderates or strengthens the relationship between green image and sustainability report and Financial Performance moderates or strengthens the relationship between green communication and sustainability report.